2001
DOI: 10.1179/016164101101199405
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility evaluation of dura mater substitutes in an animal model

Abstract: Dura-Guard Dural Repair Patch, PRECLUDE Dura Substitute, and Codman ETHISORB Dura Patch were evaluated in a six-month dural tissue reaction study in rabbits. Bilateral craniotomy was followed by subdural implantation for each dura mater substitute. The surgical procedure for the sham control group was the same except that no material was implanted. Implantation of all of these dura mater substitutes for 28, 91, or 182 days post-implantation did not result in any deaths or clinical neurobehavioral abnormalities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 7 publications
2
32
0
Order By: Relevance
“…The porous structure of the vicryl fleece permits an immigration of endogenous tissue, the undyed PDS-thread is intended to support fluid impermeability and minimize the formation of cortical adhesions. Futher studies [26,27] in animals and humans analysed the biocompatibility of vicryl fleece in six month follow up examinations and it was generally characterized by low-grade granulomatous inflammation and initial adhesions to the brain surface. The three-dimensional structure of this implant acted as a scaffold to guide the development and integration of a 'replacement' dura mater.…”
Section: Discussionmentioning
confidence: 99%
“…The porous structure of the vicryl fleece permits an immigration of endogenous tissue, the undyed PDS-thread is intended to support fluid impermeability and minimize the formation of cortical adhesions. Futher studies [26,27] in animals and humans analysed the biocompatibility of vicryl fleece in six month follow up examinations and it was generally characterized by low-grade granulomatous inflammation and initial adhesions to the brain surface. The three-dimensional structure of this implant acted as a scaffold to guide the development and integration of a 'replacement' dura mater.…”
Section: Discussionmentioning
confidence: 99%
“…Although histological analysis demonstrated slight advantages for cell-loaded PGPD in regard to local bone healing within the transplantation area, the roentgenograms showed that the presence of PGPD did not enhance the fusion rate compared to periosteal cells with fibrin and without PGPD. 51 In contrast to these findings, Barbolt et al 6 tested the in vivo biocompatibility of PGPD and reported a low-grade granulomatous inflammation within the first 6 months and a complete resolution of the inflammatory reaction after complete bioabsorption of PGPD. It is hypothesized that these findings may be based not only on a low initial biocompatibility of PGPD but also on in vivo degradation effects.…”
Section: Osteoinductivitymentioning
confidence: 97%
“…20,38,66 Diaphyseal canal restrictors containing polydioxanone are used in cemented femoral hip arthroplasty and polydioxanone fleeces are applied to reconstruct bony defects in maxillofacial and neurosurgeries. 6 Although all of these three biomaterials have already been applied in bone reconstructive surgery for many years, there is a lack of data with regard to the in vitro osteogenic potency and adherence potency for MSCs. Furthermore, it has been shown by several authors 35,36,52 that dexamethasone-, ascorbic acid-, and β-glycerolphosphate (DAG)-supplemented culture media promote osteoblastic differentiation of MSCs in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported to be completely resorbed after a period of three months. The material is replaced with fibrous collagenous tissue, and minimal inflammation is associated with this process [14,[19][20][21][22]. Subsequently, indications for its use were extended to the orbital floor [6,14].…”
Section: Introductionmentioning
confidence: 99%